2008
DOI: 10.1002/glia.20706
|View full text |Cite
|
Sign up to set email alerts
|

Methylprednisolone inhibits the expression of glial fibrillary acidic protein and chondroitin sulfate proteoglycans in reactivated astrocytes

Abstract: Reactive gliosis caused by post-traumatic injury often results in marked expression of chondroitin sulfate proteoglycan (CSPG), which inhibits neurite outgrowth and regeneration. Methylprednisolone (MP), a synthetic glucocorticoid, has been shown to have neuroprotective and anti-inflammatory effects for the treatment of acute spinal cord injury (SCI). However, the effect of MP on CSPG expression in reactive glial cells remains unclear. In our study, we induced astrocyte reactivation using alpha-amino-3-hydroxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 56 publications
1
35
0
4
Order By: Relevance
“…Moreover, suppression of astroglial scar formation enhances axonal regeneration and functional recovery after spinal cord injury [42]. An anti-astroglial effect was also demonstrated for methylprednisolone, a synthetic glucocorticoid, inhibiting the expression of GFAP in reactivated astrocytes [43].…”
Section: Multiple Effects Of Dex On Npcsmentioning
confidence: 87%
“…Moreover, suppression of astroglial scar formation enhances axonal regeneration and functional recovery after spinal cord injury [42]. An anti-astroglial effect was also demonstrated for methylprednisolone, a synthetic glucocorticoid, inhibiting the expression of GFAP in reactivated astrocytes [43].…”
Section: Multiple Effects Of Dex On Npcsmentioning
confidence: 87%
“…Astrogliosis is a characteristic inflammatory reactive response of astrocytes after SCI. Reactive astrogliosis may impair axonal regeneration and functional neuronal recovery [6,9,16]. The expression of GFAP indicates hypertrophy and proliferation of astrocytes after neurological insults.…”
Section: Curcumin Can Attenuate Gfap Expression After Scimentioning
confidence: 99%
“…Currently, methylprednisolone is the only recognized therapy for SCI, and its neuroprotective effect appears to be mediated via the inhibition of inflammatory reactions and lipid peroxidation [16]. However, the therapeutic effect of methylprednisolone is relatively minor [6], and the side effects associated with methylprednisolone are significant, including gastrointestinal bleeding, gastritis, and Cushing's syndrome [17].…”
Section: Introductionmentioning
confidence: 98%
“…17,18,22,23,25,43 This in turn has been thought to result in preservation of neurons, axons, myelin, and intracellular organelles, including the mitochondria and nucleus. 30,31 However, more recent studies have suggested that methylprednisolone acts preferentially on glia and has less of an effect on neurons, 33 and seems to have a significant impact on glial activation, thereby reducing the production of inhibitory chondroitin sulfate proteoglycans 36 and possibly facilitating an environment more suitable for regeneration.…”
Section: 6mentioning
confidence: 99%